(3GdhGVM aj eTcdGJ TYQ GdeJfHjs - (3CHj GdbGSe YHO Gddg Hf YHO GdQMef GdCUagGfjs; (3GdeJfHj , CHh GdWjH,J (B354 (3g` s
(3ChdgG (B:s
(3Ef Chdi eG GSJfLMJ Hg GdWdHg, hGSJOQcJ Hg GdHZjI, MeO Gddg Ld KfGDg hcGf HYV CfTGA NOeJg hCZPjGA fYeJg s
(3BNQgG (B:s
(3hfaS GdSjha gj MOGFO efShHI Edi GdgfO dCfgG JWHY HgG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3cGf GdeDda MjkG SfI (B380(3g```s
(3de oJbQC Ydi eDdagG hgfGc THgI JOdjS dCf NW GdeNWhWI djS ef NWhW GdbQf GdQGHY GdgLQj hHHYV ChQGbgG JbWjY hWeSs
(3jdjg efJNHGJ COHjI ef GdTYQ hGdfKQ HNW GdfGSN faSgs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs